ANALISIS MODEL INTEGRASI ILMU DAN AGAMA DALAM PELAKSANAAN PENDIDIKAN DI SEKOLAH DASAR ISLAM BANDAR LAMPUNG - FITERIANI, IDA (Universitas Islam Negeri Raden Intan Lampung, 2014)
The educational objective of this study to determine implementation of the integration of science in education at Al-Azhar Elementary School 1 Bandar Lampung, SDIT Permata Bunda 3 Bandar Lampung, and Elementary School Muhammadiyah 1 Bandar Lampung, as well as knowledge integration model is implemented. research methods using qualitative methods with a descriptive approach. Purposively selected study site. The results showed (a) the integration model which is implemented in the implementation of science education at Al-Azhar Elementary School 1 Bandar Lampung Islamic modernization model, (b) integration model is implemented in the implementation of science education in SDIT Permata Bunda 3 Bandar Lampung purification using the model, and (c) integration model is implemented in the implementation of science education in Elementary School Muhammadiyah 1 Bandar Lampung using neo-modernism.